2017
DOI: 10.1002/da.22650
|View full text |Cite
|
Sign up to set email alerts
|

Are there sensitive periods when child maltreatment substantially elevates suicide risk? Results from a nationally representative sample of adolescents

Abstract: Background Although child maltreatment is a well documented risk factor for suicidal behavior, little is known about whether the timing of child maltreatment differentially associates with risk of suicidal ideation, suicide plans, or suicide attempts. The goal of this study was to examine whether a first exposure to physical or sexual abuse during specific developmental periods significantly elevated risk for suicidal behavior in adolescents. Methods Data came from the National Comorbidity Survey Adolescent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
48
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 45 publications
1
48
1
1
Order By: Relevance
“…Early age of sexual abuse has been associated with higher suicidal intent (Lopez‐Castroman et al., ). However, a more recent study found that the timing of physical and sexual abuse was not associated with subsequent suicidal behavior (Gomez et al., ). We did not collect information about medication use on the day of testing, which could impact the results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early age of sexual abuse has been associated with higher suicidal intent (Lopez‐Castroman et al., ). However, a more recent study found that the timing of physical and sexual abuse was not associated with subsequent suicidal behavior (Gomez et al., ). We did not collect information about medication use on the day of testing, which could impact the results.…”
Section: Discussionmentioning
confidence: 99%
“…Suicide risk is elevated in individuals with psychiatric disorders such as mood disorders, chronic psychotic disorders and alcohol and substance use disorders (Harris & Barraclough, ). Childhood maltreatment has been associated with higher risk for psychiatric disorders and suicidal behavior (Anda et al., ; Gomez et al., ; Liu et al., ; Nemeroff, ; Short & Nemeroff, ).…”
Section: Introductionmentioning
confidence: 99%
“…Brown, Cohen, Johnson, & Smailes, 1999;Castellv ı et al, 2017;Fergusson, Boden, & Horwood, 2008;Fergusson, Horwood, & Lynskey, 1996;Nelson et al, 2002). Sexual abuse has been shown to have longerterm effects than physical abuse (Fergusson et al, 2008), another potent risk factor for suicidal ideation and attempt (Dunn, McLaughlin, Slopen, Rosand, & Smoller, 2013;Gomez et al, 2017). Although less frequently studied, emotional abuse also has been shown to increase likelihood of suicidal ideation in older children and adolescents controlling for covariates such as history of suicidal ideation, depressive symptoms, and in some cases controlling for sexual and physical abuse (Gibb et al, 2001;Miller et al, 2016).…”
Section: Environmental Risk Factors and Correlatesmentioning
confidence: 99%
“…Инцест связан с СП детей и подростков [99]. У сексуального насилия более долгосрочные последствия, чем физическое [90], будучи сильнейшим фактором риска СП [100,101] независимо от социальноэкономического статуса семьи, диссоциативных симптомов молодежи, негативных жизненных событий, симптомов психического здоровья, разлуки с близкими, тюремного заключения, уровня образования и изменения в попечителе. Риск попытки самоубийства в 15 раз выше у подростков мужского пола, ставших жертвами сексуального насилия, чем девочек [102].…”
unclassified
“…Incest is associated with SB of children and adolescents [99]. Sexual violence has more long-term consequences than physical [90], being the strongest risk factor for SB [100,101], regardless of the socioeconomic status of the family, dissociative symptoms of youth, negative life events, symptoms of mental health, separation from relatives , imprisonment, level of education and change in trustee. The risk of suicide attempt is 15 times higher in male adolescents who are victims of sexual violence than girls [102].…”
mentioning
confidence: 99%